Dealing with Future Deals in Light of Bahraini Civil Law: An Analytical Study - Almekhlafi, Abdullah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study addresses the topic of dealing with future deals in the context of Bahraini civil law. Its aim is to elucidate the Bahraini legislator’s stance on dealing with future deals, where legislation, including Bahraini law, has established rules and provisions governing the process of future contracts, aiming to facilitate dealing in these contracts. The study adopts a descriptive-analytical approach through analyzing legal texts related to the conditions and validity of sales contracts and specific legal texts concerning future sales in Bahraini law. The study concludes, in its findings, the permissibility of dealing with future deals according to specific criteria as a general principle, while disallowing it in exceptional cases. The Bahraini legislator has effectively regulated this type of dealing by prohibiting it in exceptional circumstances aimed at protecting the parties involved from certain detrimental actions that could occur in future contracts, such as dealing with the inheritance of a living person, or dealing based on extreme ignorance, which constitutes a form of significant deception that may lead to the high likelihood of the deal not materializing due to the absence of the sold item in the future. Prohibiting dealing in things contingent upon chance occurrences. The study recommends the necessity of interpreting and defining the meaning of prohibited chance occurrences in dealing with future deals according to Bahraini legislation.